2012
DOI: 10.1109/tbcas.2012.2226334
|View full text |Cite
|
Sign up to set email alerts
|

16-Channel CMOS Impedance Spectroscopy DNA Analyzer With Dual-Slope Multiplying ADCs

Abstract: We present a 16-channel, mixed-signal CMOS DNA analyzer that utilizes frequency response analysis (FRA) to extract the real and imaginary impedance components of the biosensor. Two computationally intensive operations, the multiplication and integration required by the FRA algorithm, are performed by an in-channel dual-slope multiplying ADC in the mixed-signal domain resulting in minimal area and power consumption. Multiplication of the input current by a digital coefficient is implemented by modulating the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…Although there are many different circuit topologies that can implement EIS [23]- [25], generally they all apply small amplitude (<10 mV) voltage sinusoids of varying frequencies (0.1 Hz -100 kHz) between a two electrode cell and record the resulting current. For each frequency, the magnitude and phase change is calculated and used to find the complex impedance ultimately forming an impedance spectrum that can be fitted to the Randles circuit.…”
Section: ( )mentioning
confidence: 99%
“…Although there are many different circuit topologies that can implement EIS [23]- [25], generally they all apply small amplitude (<10 mV) voltage sinusoids of varying frequencies (0.1 Hz -100 kHz) between a two electrode cell and record the resulting current. For each frequency, the magnitude and phase change is calculated and used to find the complex impedance ultimately forming an impedance spectrum that can be fitted to the Randles circuit.…”
Section: ( )mentioning
confidence: 99%
“…For genomic detection, ssDNA segments which are complementary to the intended target sequence are used [1]. More complex biological molecules can be used for protein detection such as antibodies and other binding proteins [2], [3].…”
Section: Recognitionmentioning
confidence: 99%
“…EIS is thereby, a very useful non-invasive tool to observe the properties of such cell layers and tissues; it is conducted by exciting the observed system with an alternating voltage and with a small amplitude (typically 10 mV pp ) over a certain frequency range of interest, commonly from a few Hz up to even a few M Hz, depending on the application [3], [1]. A measurement of the current flow, due to this excitation, gives the equivalent impedance and phase shift of the system under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, routing of the higher frequency sinusoidal signals (M Hz region) and distributing it to various electrodes limited system performances due to parasitic effects. [3] integrated an 8-bit R2R DAC, but the reported power and area consumption showed that this could not be realized several times for high channel count EIS, but that it rather had a dominating impact on power and area of the overall IC. Another issue in SoA is that the single DACs need to be able to drive individual, but also a multitude of electrodes, which puts stringent requirements on the DAC.…”
Section: Introductionmentioning
confidence: 99%